Industry 4.0 vision for the supply of energy and materials : enabling technologies and emerging applications - Sharifzadeh, Mahdi (John Wiley & Sons, Inc., 2022)
"Industry 4.0 paradigm is a strategic initiative that uses advancements in intelligent instrumentation and internet to promote digital transformation in industry. It integrates physical and computational environments and envisages a smart ecosystem that creates business growth in the supply chain. Connectivity is an essential prerequisite for the highly anticipated Industry 4.0 and provides seamless communication between all instances involved in the connected economy. In this context, wireless communication and cellular networks are key technologies that support the vision of Industrial Internet. Different wireless technologies and standards are proposed to handle communications in production and process areas. In this chapter we will review requirements of connectivity in Industry 4.0 era and elaborate multiple wireless communication technologies, cellular networks and Machine Type Communication (MTC) for industrial systems"--